Measuring and analyzing the angular momentum produced in the application of the judo throwing technique Osoto-Gari - Liu, L. J.; Ishii, T.; Deguchi, T.; Shinya, M. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to analyze the angular momentum in the judo throwing technique osoto-gari. Ten male judo athletes participated in this study. The kinematic and kinetic data were collected using a three-dimensional motion capture system and two force plates. We analyzed the resultant angular momentum of a system that includes both the thrower and the faller. The counterclockwise angular momentum continuously increased during the throwing phase, indicating the torque was always acting toward the throwing direction. Our results demonstrated that the torque was associated with the horizontal GRF during the early swing phase and it was associated with the Y-axis moment arm during the late throwing phase.